Profiles evolutionary design and evaluation of mixing performance of screw elements for intermeshing counter-rotating twin-screw kneader. (October 2016) - Wei, Jing; Zhou, Dongming; Zhang, Aiqiang; Yang, Yuliang; Chen, Dabing
The profile designs of screw elements are very crucial to improving the mixing performance for the intermeshing counter-rotating twin-screw kneader. In order to find the inherent law among different profiles of screw elements and to derive a mathematical model which evolves different types of end cross-section profiles of screw elements, a universal mathematical model of end cross-section profiles of screw elements is presented in this work. Different types of profiles of screw elements, including those traditionally used can be obtained by evolutionary design method after changing the tooth number of female and male elements and other design parameters. Several typical screw elements with different types of end cross-section profiles are selected to analyze the mixing performance. Spatial flow patterns in flow channel of the screw elements are presented with particle tracking analysis by using mesh superposition technology. The mixing performance of different screw elements including distributive and dispersive mixing, contrastive analysis for some parameters, such as residence time distribution density function, segregation scale, rate of stretching, rate of shear, etc. are proposed. The results in this paper provide a data basis for the profiles selection of screw element for intermeshing counter-rotating twin-screw kneader.